Pendampingan Pemanfaatan limbah Urin Kambing Menjadi POC: Pengabdian di Desa Wirotaman Kecamatan Ampelgading, Kabupaten Malang, Provinsi Jawa Timur. - Agus Wiastono; Ferra Eka Ramadhani (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
Keeping goats is one of the primary activities of the business group in Wirotaman Village, Ampelgading District, Malang Regency. Keeping goats has various advantages, including: 1) easy to get and inexpensive feed; 2) simple care; and 3) counting the number of children produced by the parents. Goat pee may also be utilized as a liquid organic fertilizer. Goat pee is one of the most common organic fertilizers used by farmer groups in Wirotaman Village, but its full potential has yet to be realized. The goals of this activity are to (1) use waste created from goat urine; and (2) enhance goat breeder group management. Education and facilitation are the methods employed. The following: (1) providing counseling to groups of goat breeders for the manufacture of organic fertilizer derived from goat urine; (2) the introduction of fertilizer-making equipment; (3) assistance for training on the use of tools; group motivation; and marketing management of organic fertilizer products derived from goat urine are all examples of education. Facilitate by supplying the group with the necessary instruments for the production of organic fertilizers. This endeavor is being made to boost the economic added value for goat producers by using waste created from goat pee.